Advances in mitochondrial dysfunction in radiation tissue injury - Rong, Jianhuang; Yu, Qiujie; Huang, Guilin; Wang, Yueyue; Zhang, Nini (Frontiers in Physiology, 2025)
Radiation-induced tissue injury is a major limitation in cancer radiotherapy, often leading to collateral damage in healthy tissues. While the nucleus has long been considered the principal target of ionizing radiation, emerging evidence underscores the pivotal role of mitochondria in mediating radiation-induced damage. This review provides a comprehensive overview of mitochondrial dysfunction in various irradiated tissues, including the intestine, hematopoietic system, heart, lung, brain, and skin. Key mitochondrial alterations—such as disrupted dynamics, impaired energy metabolism, excessive reactive oxygen species (ROS) production, and activation of apoptotic and senescence pathways—are highlighted as central mechanisms underlying radiation pathology. Additionally, we summarize the involvement of crucial signaling pathways such as AMP-activated protein kinase/peroxisome proliferator-activated receptor gamma coactivator 1-alpha (AMPK/PGC-1α),nuclear factor erythroid 2–related factor 2/antioxidant response element/mitochondrial transcription factor A (Nrf2/ARE/TFAM), and NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome in regulating mitochondrial responses to radiation stress. A deeper understanding of mitochondrial involvement provides novel avenues for radioprotection and therapeutic interventions in oncology.